Pengembangan UMKM Cho Cweet melalui Program Community Development - Evander Hosea, Jason; Filbert, Keandre; Jasmine, Livia; Darmawan, Putu; Stella Susanto, Yohana; Zulandari, Peni (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2022)
Community Development is an entrepreneurship-based Community Service program with the aim of increasing partners’ understanding of basic business management, motivation in running a business, and increasing welfare in the form of income growth through business development. Community Development 2021 will be carried out online. The group had the opportunity to provide assistance with a Micro, Small and Medium Enterprises, “Cho Cweet” as a partner. In providing assistance, the group assists in the development of one of the partner's products, optimizes online sales, and conducts partner financial analysis. The results we get are quite good and our partner felt very helpful with the guidance of this Community Development program. Our partner’s income also increased during the mentoring program